POLITICAL TELEVISION’S ADDICTION: CAUSES AND CONSEQUENCES - Головчук, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
Political dependence TV is a real threat to the political culture and democratic television channels. For political reasons, according to belong: the limited rights of journalists and non-fulfillment of norms applicable laws; difficult economic situation of TV organizations, the problem of the use of television as a means of coming to power, unprofessional team of journalists, lack of journalistic ethics, the danger of lawsuits for „moral damage” manipulation around the studios licensing, lack of management to promote their own product on national television channels, etc.